A First Attempt at Modelling Red Deer (Cervus elaphus) Distributions Over Europe. (14th July 2014) - Wint, William; Morley, David; Medlock, Jolyon; Alexander, Neil S
The presence of red deer may be a contributing factor within the ecological and epidemiological systems contributing to the risk and spread of a range of vector-borne diseases. Deer are important hosts for many vectors, and may therefore serve as a focal point or attractant for vectors or may themselves become a reservoir for vector-borne disease. Three spatial modelling techniques were used to generate an ensemble model describing the proportion of suitable red deer habitat within recorded distributions for Europe as identified from diverse sources. The resulting model is therefore an index of presence, which may be useful in supporting the modelling of vector-borne disease across Europe.